Electronic application for oral health school programme enhances the quality of the information in dental health data records - Nurul Fatikhah; Gilang Yubiliana; Fedri Ruluwedrata Rinawan (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Dental and oral health problems among elementary students can be resolved through an oral health programme in schools. The main factor that inhibited this scheme was that the recording and reporting still employed a manual system, making it less effective and efficient. The electronic application of this programme can help managers to complete both of these tasks. Purpose: This study’s aim is to assess the effectiveness of the electronic application that is utilised in the oral health school programme to increase the quality of the information relating to the recording of dental health data in schools. Methods: This study used a pre-test and post-test one-group design, and the sample consisted of 37 oral health programme managers in schools who were chosen via simple random sampling. The data in this study was analysed using the Wilcoxon signed-rank test. Results: The results showed that the use of the electronic application as part of the oral health scheme influenced the quality of the information when details were recorded and reported. This can be seen in the rise in the standard of the information that was noted and disclosed when comparing data before and after using the electronic application; the average value of 1.54 (standard deviation=1.45) increased to an average value of 3.58 (standard deviation=2.84) with a significance level of 0.000 (p<0.05). Conclusion: The electronic application used in conjunction with the oral health programme was effective in raising the quality of dental health records in schools.